Co-expression Network Revealed Roles of RNA m6A Methylation in Human β-Cell of Type 2 Diabetes Mellitus - Chen, Cong; Xiang, Qing; Liu, Weilin; Liang, Shengxiang; Yang, Minguang; Tao, Jing (Frontiers in Cell and Developmental Biology, 2021)
RNA m6A methylation plays an important role in the pathogenesis of type 2 diabetes mellitus (T2DM). RNA modifications and RNA-modifying regulators have recently emerged as critical factors involved in β-cell function and insulin resistance, including ‘writers’, ‘erasers’ and ‘readers’. However, their key roles in regulating gene expression in T2DM remain unclear. The construction of co-expression network could provide a cue to resolve this complex regulatory pathway. We collected the transcriptome datasets of β-cell in diabetic patients, calculated the partial correlation coefficient, excluded the influence from control variables of diabetes related genes, and identified the genes significantly co-expressed with m6A regulators. A total of 985 genes co-expressed with m6A regulators (Co-m6AR) were identified, which were enriched in metabolic process, MAPK and EGFR signaling pathways. Some of them have been confirmed to play a pivotal role in T2DM, including CCNL2, CSAD, COX5A, GAB2, MIRLET7I, etc. Further, we analyzed the m6A modification characteristics of Co-m6AR in β-cell and identified 228 Co-m6AR containing m6A methylation sites, involving in several key signaling pathways regulating T2DM. We finally screened out 13 eQTL-SNPs localized in Co-m6ARs, and 4 have been reported strongly associated with diabetes, including GAB2, LMNB2, XAB2 and RBM39. This co-expression analysis provides important information to reveal the potential regulatory mechanism of RNA m6A methylation in T2DM.